INCIDENCE AND DEMOGRAPHICS MANIFESTATIONS OF COLORECTAL CANCER IN SULAIMANI CITY - Ali, Rozhgar Rashid; Ameen, Hazha Abdulla Mohammed; Nidhamalddin, Sara Jamil; Hassan, Mohammed Abdalwahab; Qadir, Azhin Ali (Journal of Sulaimani Medical College, 2022)
Background Colorectal cancer is the third most common malignancy. However, there is a shifting paradigm and clinical manifestation related to the early presentation. Objectives To know the incidence and evaluate the demographic manifestations of colorectal cancers in Sulaimani. Patients and Methods A retrospective cross-sectional study was performed on 516 patients admitted to Hiwa Hospital from January 2015 to December 2019. Data of patients were retrieved from the hospital database. Inclusion criteria were patients aged ≥18 years who had colorectal cancers. Demographic features, including ages and gender, clinical manifestations, abdominal pain, bleeding per rectum, constipation, and personal and family history of malignancy, were recorded. Also, the location, stages, and histopathological features of cancer were recorded. Results The incidence of colorectal cancers was 40.3 per 100000 persons per year. There was no significant shifting of colorectal cancer incidence toward younger ages (p-value = 0.605). The majority of patients were aged >50 years, and the male: female ratio was (1.1:1). Most patients were presented with abdominal pain, bleeding per rectum, and constipation; 64.5%, 57.2%, and 41.9%, respectively. A significant association was found between grades and presentations. There was a significant association of polyp findings on colonoscopy with their staging. Conclusion The incidence of colorectal cancers in Sulaimani did not significantly shift toward younger ages but slightly increased. Colorectal cancer had near-the-same gender distribution, and most patients had abdominal pain and bleeding per rectum
Keywords: Colorectal cancer; Colorectal epidemiology; Colorectal incidence; Demographic features